Race and Ethnicity in Arkansas : New Perspectives - Kirk, John A., 1970- (Book collections on Project MUSE., 2014)
John A. Kirk is George W. Donaghey Professor and chair of the History Department at the University of Arkansas at Little Rock. He is the author or editor of several books, including Martin Luther King, Jr. and the Civil Rights Movement and Arsnick: The Student Nonviolent Coordinating Committee in Arkansas.